Relationship of Transformational Leadership Style of Head Room and Performance of Implementing Nurse in the Inpatient Room at Bandung General Hospital and Prof. Dr. Boloni Medan General Hospital - Sahala Bungaran Silaen; Destanul Aulia; Siti Saidah Nasution (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze relationship of transformational leadership style of head room and performance of implementing nurse in the Inpatient Room at Bandung General Hospital and Prof. Dr. Boloni Medan General Hospital. This research is a quantitative research with associative correlative research design. The population in this study are head room of the Inpatient Room at General Hospital as many as 31 people consisting of 17 people at Bandung General Hospital and 14 people at Prof. Dr. Boloni Medan General Hospital. The sample in this study is the entire population as the research sample (total population) as many as 31 head room of the Inpatient Room at Bandung and Prof. Dr. Boloni Medan General Hospital. The data analysis method used bivariate analysis. The results show that there is relationship of transformational leadership style of head room and performance of implementing nurse in the Inpatient Room at Bandung General Hospital and Prof. Dr. Boloni Medan General Hospital.